ANALYSIS OF THE MOVEMENT OF COTTON SEEDS UNDER THE INFLUENCE OF A SCREW CONVEYOR - Sarbarov, Khusanboy; Jumaniyazov, Kadam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the results of an experiment conducted to analyze the movement of cotton seeds under the influence of a screw conveyor. It should be noted that an increase in work productivity leads to an increase in the pressure force on the cotton seeds on the surface of the screw, which in turn causes seed clogging. Therefore, optimizing work efficiency by selecting the appropriate screw rotational speed based on its angular velocity is of great importance. During the study, it was observed that correctly choosing the screw speed corresponding to different productivity values (Q1, Q2, Q3) helps to reduce seed clogging.